Investigasi Keterampilan Kata Heian Shodan Menjelang Ujian Kenaikan Tingkat Sabuk: Studi Cross Sectional - Firman Septiadi; Bachtiar (Indonesian Journal of Physical Activity, 2023)
The purpose of this study was to find Heian Shodan kata skills approaching of test the belt level. The research method in this study used survey with cross sectional study. The population in this study were PJKR students karate class with used sample jenuh techniques. The results in this study have a variety of criteria, namely 12 very good students, 13 good students and 3 moderate students of Heian Shodan kata skills. The average student has a good criterion in the skills of Heian Shodan kata. The conclusion in this study is that students are ready to take test the belt level.